The Proposed Polish Advertisement Levies – An Efficient Source of Public Income or Instruments of the Political Battle? - Duda-Hyz, Michalina (Review of European and Comparative Law, 2022)
This article analyses the bill of 2nd February 2021 on additional revenues of the National Health Fund, the National Fund for the Protection of Historical Monuments and the establishment of a Fund for the Support of Culture and National Heritage in the Media Area. The draft legislation, the announcement of which has triggered an unprecedented blackout protest in private media as well as a mass anti-government protest on the Internet, provides for the introduction of new public levies called advertisement contributions and the establishment of a new state special-purpose fund – the Fund for the Support of Culture and National Heritage in the Media Area. The aim of the article is to identify and present those provisions of the draft act which have evoked most controversies and have given rise to the stiff social resistance to the proposal. The first part of the paper is devoted to the assessment of the regulations within the context of the objective of the bill that was declared by the drafters in the legislative rationale. The analysis carried out has supported the assumption that providing adequate finances for those special-purpose funds that are strongly involved in remedying the consequences of the SARS CoV-2 epidemic was not a genuine purpose of the bill. It also leads to the conclusion that there is no constitutional justification for such a special-purpose levy. In the second part, the controversies over technical components of the advertising levies have been presented and analysed. On the basis of this analysis, it is possible to conclude that some of the qualitative and quantitative elements of the so-called advertisement contributions may give rise to interpretative doubts. The implementation of the research objectives made it possible to formulate a thesis that the advertisement contributions, as drafted, would not be efficient instruments of fair taxation of digital economy but rather would form instruments for achieving certain political objectives.